STUDENTS’ PERCEPTION OF ONLINE ENGLISH EXAMS DURING THE COVID-19 PANDEMIC: A SURVEY STUDY AT A PHARMACEUTICAL VOCATIONAL HIGH SCHOOL IN RIAU - Rahmatilla, Fitri; Hadi, Abdul (English Study Program University of Pasir Pengaraian, 2023)
This study aimed at investigating students’ perception of online English exam during the Covid-19 pandemic at a pharmaceutical vocational high school in Riau. The study also explored the factors that influence students’ perception of online English exams. Employing a survey study design, it was found that students at the pharmaceutical vocational high school in this study were not similar in their perception to online English exams though they studied in the same school. The same educational and learning environment did not contribute to the students having similar perception to online English exams. Although a little bit more than half (51.7%) of the students had positive perception to online English exams, there is a significant number (46.6%) of the students who had negative perception to online English exams. Only 1 student had neutral perception to online English exams. This finding suggests that students may have different perceptions to a certain way of doing assessment or learning despite the fact that they study in the same school. With regard to factors influencing the students’ perception of online English exams, it was found that purpose of online English exams is a major influencing factor. Another major influencing factor, but with lower degree of influence, is institutional and environmental support to online English exams. These two major influencing factors are followed by less influencing factors, which include design of online English exams and security of online Exam.